2021
DOI: 10.1371/journal.pone.0245855
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals key transcription factors associated to drought tolerance in a wild papaya (Carica papaya) genotype

Abstract: Most of the commercial papaya genotypes show susceptibility to water deficit stress and require high volumes of irrigation water to yield properly. To tackle this problem, we have collected wild native genotypes of Carica papaya that have proved to show better physiological performance under water deficit stress than the commercial cultivar grown in Mexico. In the present study, plants from a wild Carica papaya genotype and a commercial genotype were subjected to water deficit stress (WDS), and their response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Drought tolerant papaya was shown to have greater photosynthetic II (PSII) efficiency than susceptible ones. Susceptible plants displayed greater leaf abscission, less turgid shoots, and lower plant growth than those of more tolerant ones [30].…”
Section: Papaya Responses To Environment Stressesmentioning
confidence: 90%
See 1 more Smart Citation
“…Drought tolerant papaya was shown to have greater photosynthetic II (PSII) efficiency than susceptible ones. Susceptible plants displayed greater leaf abscission, less turgid shoots, and lower plant growth than those of more tolerant ones [30].…”
Section: Papaya Responses To Environment Stressesmentioning
confidence: 90%
“…Drought susceptible plants displayed greater leaf abscission, less turgid shoots, and lower plant growth than those of tolerant papaya. Molecular analysis identified six transcription factors including CpHSF, CpMYB, CpNAC, CpNFY-A, CpERF, and CpWRKY that were highly expressed in tolerant papaya [30]. These genes were reportedly also involved in drought tolerance in rice and maize [31,32].…”
Section: Agronomic Characteristicsmentioning
confidence: 99%
“…Furthermore, all four sets of BRs showed that the “extracellular region” and “starch metabolic cycle,” showing two lines, included similar drought blockage components ( Zenda et al., 2018 ). PCA revealed the identical characteristics of both plants, including the relevance of numerous limitations ( Estrella-Maldonado et al., 2021 ). Each rate is shown with the eigenvalues in the PCA evaluation, indicating that these characteristics are accurate and connected to the other rates ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maize plant has a simple structure, and its unique germplasm makes it a more valuable crop than other cereals ( Corso et al., 2015 ). Although significant progress has been made in investigating maize response to drought stress, previous studies have focused on physiological and metabolic or single-trait responses ( Estrella-Maldonado et al., 2021 ). The high-throughput sequencing frameworks that rely on the RNA level and their analysis results have profoundly changed our viewpoint on the extent and heterogeneity of the maize transcriptome to a substantial degree over the last decade ( Faghani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 40 potential microRNAs related to salinity stress and their target transcripts were characterized in guava [ 103 ]. Transcription factors regulating drought stress tolerance were examined in papaya and belong to TF families such as CpHSF , CpMYB , CpNAC , CpNFY-A , CpERF and CpWRKY [ 63 , 191 ]. Though there is no genetic information on drought stress related mechanisms in jackfruit, SSR markers developed and QTLs identified for drought tolerant root traits in mulberry can be studied for assessing the jackfruit germplasm, as they showed 79.25% transferability to cross species [ 192 ].…”
Section: Abiotic Stressmentioning
confidence: 99%